Environmental and economic optimization by carbon capture process applied to MEA chemisorption system - Ferrufino, G. L.A.A. [UNESP]; Luna, C. M.R. [UNESP]; Balestieri, J. A.P. [UNESP]; Carvalho, J. A. [UNESP] (My University, 2009)
The capture of carbon dioxide (CO2) from the flue gas of coal fired power plants can be performed using monoethanolamine (MEA,(C2H4OH)NH2), which is a technically viable strategy in the short to medium term for atmospheric CO2 emissions mitigation. However, the production cost is currently high for a 100% capture, which makes the process economically unfeasible. This paper proposes an optimization procedure to analyse the capture capacity for a flow exhaust gas. In this paper, the objective is to analyze the CO2 capture process aiming at the cost minimization and profit maximization, which is given by the CO2 percentage captured assuming different penalty taxes for the CO2 emitted. To demonstrate the method, a hypothetical flue gas composition was assumed: 14% CO2 concentration in the exhaust gas, as it happens in coal power plants. In this case, the flue gas flow rate was considered to be 70,000 kmol/h, which corresponds to a 500 MW coal fired power plant. The optimization results estimated that for a penalty tax of zero for CO2 emitted and a price of 14,7 €/TnCO2 captured (average price of carbon credit for 2008), the range of CO2 capture will be in the range 42-70%. When the penalty tax increases, the range for CO2 capture decreases. When the penalty tax attains 10 €/TnCO2 emitted, the process becomes economically unfeasible. For this penalty tax, the process becomes economically feasible for values of carbon credit higher than 20 €/TnCO2 captured.
Keywords: Carbon capture; CO2 chemisorptions system; Optimization process